Studi Deskriptif Tentang Usia, Tingkat Pendidikan, dan Pekerjaan terhadap Keikutsertaan Pasangan Usia Subur dalam Program KB di Desa Gandu Majalengka - Tegar Purnama Nurul Hakim; Susy Olivia Lontoh (PPNI UNIMMAN, 2025)
This study aims to describe the relationship between age, education, and occupation with the participation of Couples of Reproductive Age (PUS) in the Family Planning (KB) program in Desa Gandu, Majalengka. The study design used is a descriptive observational design with a cross-sectional approach. The sample of this study consisted of 440 PUS recorded in the village administration and Puskesmas between January and June 2025. The results of the study showed that older age (25-34 years), lower education, and the occupation of housewives (IRT) were associated with higher participation in the KB program. Most respondents with low education (SD and SMP) showed high participation in the KB program, while those with higher education showed lower participation. These findings indicate the importance of a community-based approach that involves housewives (IRT), as well as the need to improve KB counseling programs for higher-educated groups and formal workers. This study suggests that KB programs in Desa Gandu should focus more on the younger age group, formal workers, and those with higher education who still have lower participation rates.